Pengolahan kelapa jelly dan manisan kelapa di Desa Binaan Tanjung Alai Kecamatan XIII Koto Kampar Provinsi Riau - Aras Mulyadi; Dessy Yoswaty; Iesje Lukistyowati; T Ersti Yulika Sari; Niken Ayu Pamukas; Adelina Adelina (Unri Conference Series: Community Engagement, 2019)
Tanjung Alai Village is in The XIII District of Koto Kampar Riau Province, downstream of The Gulamo River with The Kampar River. The local government of Kampar Regency has develop tourism potential in Tanjung Alai Village. For example it has traction in the form of beautiful natural scenery, the distance from the city of Pekanbaru to Tanjung Alai Village about 2 hours (21 km), the catchment area, the historical site of the Muara Takus Temple, Puncak Pukatan as a climbing and Pulo Simo waterfall area. Tanjung Alai Village too has potential as rubber, oil palm, gambier, chocolate and coconut plantations. Coconut palm has opportunities with high economic value, utilized by community to diversify coconut processed products and support industrial products food preparations. The purpose of the activity is to make Tanjung Alai Village a target village from LPPM University of Riau by doing coconut jelly and candied coconut processing activities. Benefits of activities that can be used as an alternative effort to improve the welfare of the community and entrepreneurship. The method used is a combination of counseling and the practice of using coconut jelly and candied coconut. Strategic target audience in the activities of the target villages there were 25 PKK mothers. The evaluation results of the participants perception stated that it was very agreeable (59,2%) held this activity, received and practiced the training of coconut jelly and candied coconut as an opportunity for alternative income for the community. Economic analysis of processed coconut jelly amounted to IDR. 4.653.600/month and candied coconut is IDR. 2.248.800/month.